APLIKASI GOOGLE EARTH ENGINE UNTUK KLASIFIKASI HABITAT BENTIK PESISIR NONGSA BATAM MENGGUNAKAN ALGORITMA RANDOM FOREST - Prabowo, Nico Wantona; Rusli, Ari; Ghazali, Muhammad; Lubis, Muhammad Zainuddin; radityani, Fitri afina (JURNAL PERIKANAN DAN KELAUTAN, 2025)
This study aims to map benthic habitats in the coastal area of Nongsa, Batam, using Sentinel-2A satellite imagery processed using the Random Forest (RF) algorithm on the Google Earth Engine (GEE) platform. The study area includes Teluk Mata Ikan, Tanjung Bemban, and Batu Besar, Nongsa District, Batam City, Kepulauan Riau Province. Field data were obtained through snorkeling surveys and underwater photo documentation in 16-18 August 2024. The four main habitat classes that were successfully identified include coral, sand, seagrass, and rubble (dead coral fragments). The classification results show the dominance of non-living substrates in the form of sand and rubble in most of the study area, while seagrass and coral are distributed in a limited area. Validation of the classification results produced an Overall Accuracy value of 89.90%, indicating a very good level of classification accuracy and suitability. The combination of Sentinel-2A imagery, RF algorithm, and GEE has proven to be effective, efficient, and replicable for mapping tropical benthic habitats spatially and periodically as a basis for sustainable coastal area management.